Prevalence and association of Panton-Valentine Leukocidin gene with the risk of sepsis in patients infected with Methicillin Resistant Staphylococcus aureus - Noor Ilham Ahmad; Chan Yean Yean; Phiaw Chong Foo; Amira Wahida Mohamad Safiee; Siti Asma' Hassan (Elsevier, 2020)
Background: Panton-Valentine Leukocidin (PVL), is one of the virulence gene expressed by Methicillin Resistant Staphylococcus aureus (MRSA) and is known to be associated with severe form of community acquired MRSA infection. The aim of this study is to investigate its prevalence in our setting and patient's clinical outcome. Methods: A cross sectional study involve retrospective record review were done involving 90 MRSA positive isolates between November 2016 and October 2017. Multiplex PCR was performed to detect femA, mecA and PVL genes. Clinical presentation and outcomes of patients were reviewed and presented as descriptive analysis. Results: All of the 90 MRSA isolates included in this study were positive for femA and mecA genes following PCR. PVL gene was detected in 20% (n = 18) of the isolates of which 61.1% (n = 11) were community acquired infections and 38.8% (n = 7) were hospital acquired. Case distribution from community acquired infections include patients with skin and soft tissue infections (33.3%, n = 6), infected diabetic foot ulcers (16.7%, n = 3), and one patient each (5.5%, n = 1) for community acquired pneumonia and meningitis. Half of the PVL positive MRSA cases (50%, n = 9) were having sepsis and four of them succumbed to death due to severe infection. Conclusion: This study shows a high prevalence of PVL positive MRSA infection in our population. Skin and soft tissue infections accounting for the major sources. In addition, the presence of the PVL gene is associated with increased risk for developing sepsis.